Assessment of wind power generation - Wannakam, Khanittha; Jiriwibhakorn, Somchat (My University, 2018)
Wind power generation is an unstable source of renewable energy. Electricity depends on the weather at the installation location of the wind turbine. This paper presents the prediction of wind power by using the Weibull distribution and Adaptive Neuro-Fuzzy Inference System. The lowest error rates from the Adaptive Neuro-Fuzzy Inference System were 2.1912% and 4.5678%. This is the error value of the training data and the test data respectively.
Keywords: Adaptive neuro-fuzzy inference system (ANFIS); Weibull distribution; Wind power generation